PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW II BERBANTUKAN BAHAN AJAR BERMUATAN NILAI-NILAI KARAKTER TERHADAP KOMPETENSI SISWA KELAS XI SMAN 5 PADANG - Ummiatul Fitri; Yenni Darvina; Murtiani Murtiani (PILLAR OF PHYSICS EDUCATION, 2016)
Student’s achievement on competence of behavior, knowledge and sklii in Physic subject has not been in optimal results, yet. It is caused by less-motivated students while learning Physic and they do not understand well about the lesson; moreover, the learning itself is monotonous and less-attractive. So that, this research used Cooperative Learning Model, Jigsaw II, which character values in learning material is assumed to increase student’s competence in Physic. This researc used Quasi Experiment Research with Randomized Control Group Only Design. The population of this research was students of XI MIA at SMAN 5 Padang. The sample in this research was taken by Cluster Random Sampling technique; as a result, XI MIA 1 and XI MIA 5 were chosen as sample of this research which have 28 students each class. The instrumentations of this research were observation sheet and self-assessment for behavior competence, writing tes for knowledge competenece and rubric score for skill competence. For analyzing the data, the researcher used t-test at the 0,05 significance levelo for these three competences. The results revealed that the using of Cooperative Learning Model, Jigsaw II, which learning material had character values gave psitive impact on competence of behavior, knowledge and skill for students of XI MIA at SMAN 5 Padang